Quality management system (QMS) in Brisas Covarrubias Hotel, Cuba - Parra-García, Isabel Cristina (2017)
A procedure for the design of the SGC was elaborated directed to the operative processes in the hotel Brisas Covarrubias de Las Tunas, Cuba, based on the requirements raised in norm ISO 9001:2015. Finally a partial application of the procedure was made in the operative process of animation obtaining itself like results the map of processes, the flow chart, the card of process, the management of risks, the present tendencies of animation, the level of satisfaction of the client (equal to 85 %) and the index of perception of the quality of the service (in 4,25).